PEMBINAAN KARAKTER AGAMIS MELALUI PROGRAM MENTORING ANAK ASUH RUMAH ZAKAT INTEGRATED COMMUNITY DEVELOPMENT (ICD) UJUNGBERUNG BANDUNG - Aryanti, Fitriani Dewi (2015)
The establishment of religious character is needed for creating the youth people who have high intelligence, smart, and lofty morals as an effort to solve the problems that have happened the children. The purposes of the research are to describe plenning, implementation, evaluation, and also to describe the result to the orphan after getting the establishment of religious character through mentoring program at Rumah Zakat Integrated Community Development (ICD) Ujungberung Bandung. The basic theories that had chosen in this research are first, it is about PLS concept. Second, implementation activity concept that explain about planning, implementation, and evaluation activity. Third, character concept that explain about character and character education. Fourth, establishment concept that explain about range, procedur, and establishment approach. Fifth, the establishment of religious character through mentoring program that explain about the establishment of Islamic character, mentoring and the orphan. This research is using descriptive research method with qualitative approach, whereas the main instrument of collecting data is intervieworientation. The subjects who become data resource consist of an organizer, a mentor,an orphan, a parent, and two triangulan in establishment. Data analysis technique is done by reduction data, display data, and conclusion also verification. Based on result of the research which has done about establishment planning has appropriated with the purpose in realizing activity planning. The realization of establishment is done by any methods and strategies. Evaluation has appropriated with indicator achievement which has determined by oral test and writing, academic report upgrading, and also visiting their own house. The result of establishment to the orphan in this research has changed on children's attitude that looks on their daily habits as trusteeship, good deed, discipline, emphaty, honesty, cooperative, humble and respectful.